Catalytic CH4 pyrolysis promoted by the interface of a molten metal–salt hybrid system - Seo, Jeong Cheol; Park, Sunju; Park, Gyeongah; Lee, Yunjo; Han, Seung Ju; Kim, Seok Ki (Gas Science and Engineering, 2023)
Hydrogen is an important chemical feedstock and energy carrier. A promising idea for a bridging technology for net-zero carbon emission is the catalytic pyrolysis of natural gas into hydrogen and solid carbon. However, the activation of methane and recovery of the produced carbon with high purity are the main hurdles for process commercialization. In the present study, molten metal–salt layered reaction beds for methane pyrolysis were investigated to determine the effect of the interface and the optimal ratio of metal and salt. These layered catalyst beds had several advantages over pure molten metal or molten salt catalyst beds. First, the length of the molten metal layer could be minimized to a level where the methane bubbles only touch the metal–salt interface, enhancing the economic feasibility of the process. Second, the metal–salt interface could delay bubble rising in proportion to the interfacial tension. Third, the molten salt layer could wash out the residual metal traces from the produced carbon, improving the carbon purity. This study would provide hints for building economically viable catalytic pyrolysis of methane based on molten metal-salt layered reaction bed.
Keywords: Carbon recovery; Catalytic pyrolysis; CH 4; Chemical energy; Chemical feedstocks; Metal salt; Metal-salt interface; Methane pyrolysis; Molten salt; Reaction beds; Carbon recovery; Hydrogen production; Metal-salt interface; Methane pyrolysis; Molten metal; Molten salt